Reconstruction with titanium mesh following wide excision in chest wall myxofibrosarcoma: A case report. (2020) - Joalsen, Ivan; Christian, David; Rosalie, Amy; Angga, Made
Highlights: Extensive resection in chest wall malignancy is mandatory, oftentimes leaving large defects that affect normal respiration. Various materials for chest wall reconstruction are at hand but a definite guideline is not yet available. Titanium meshes provide the suitable strength, rigidity, and flexibility for a chest wall reconstruction material. Titanium mesh is a promising alternative for a chest wall reconstruction material. Abstract: Introduction: Some chest wall tumors require extensive excision that alters its stability and integrity. Various materials are available as a prosthetic albeit currently lacking in clear guidelines regarding the material of choice. Titanium-based mesh offers appropriate properties for chest wall reconstruction, making it a promising choice of prosthetic. Presentation of case: A 50-year-old male presenting with a chest lump was suspected of a chondrosarcoma of the chest wall. Preoperative pulmonary rehabilitation and smoking cessation was performed 1 month prior to surgery. After a wide excision procedure, we utilized titanium mesh as a reconstructive material. Pathology evaluation reported the examined tissue as a myxofibrosarcoma. The patient was successfully weaned off of ventilator in less than 24 h with satisfactory postoperative outcome. Discussion: The various available material has each of its strengths and drawbacks and it is crucial to choose the most fitting option to acquire better postoperative outcome as well as maintaining the quality of life. The use of titanium mesh in thoracic reconstruction has not been widely explored and reported, therefore, it is important to underline its advantages and disadvantages as a potential choice for prosthetic. Conclusion: Titanium mesh provides appropriate features for a chest wall reconstruction; therefore, it can be considered as a promising alternative material.